The Influence of Creativity and Digital Literacy on Entrepreneurial Interests in Generation Z Students - Wenny Permata Sari; Dwi Puspita Anggraini (Penerbit Goodwood, 2026)
Purpose: This study aimed to examine the influence of creativity and digital literacy on entrepreneurial intentions among Generation Z students at Bandar Lampung University. This study investigates how these two factors contribute to fostering entrepreneurial intentions among university students. Research Methodology: A quantitative survey was conducted with 97 respondents from Bandar Lampung University. The data were analyzed using multiple linear regression to assess the impact of creativity and digital literacy on entrepreneurial intention. This method allows for an understanding of the individual and combined effects of these variables on students' entrepreneurial intentions. Results: The results indicate that both creativity and digital literacy positively and significantly affect entrepreneurial intention. This effect was observed both partially and simultaneously, suggesting that the enhancement of these two factors can contribute to the development of entrepreneurial intention among Generation Z students at Bandar Lampung University. Conclusions: The findings highlight the importance of fostering creativity and digital literacy to encourage entrepreneurial intentions among university students. Limitations: The study is limited by the relatively small sample size of 97 respondents, which may not fully represent the broader population of Gen Z students. Additionally, the study was conducted at a single university, which may limit the generalizability of the findings to other universities or regions. Further research with larger and more diverse samples could provide more robust insights. Contributions: This study contributes to the entrepreneurial intention literature by exploring the roles of creativity and digital literacy in shaping the entrepreneurial mindset of Generation Z students.